Long live evil eaudiobook - Brennan, Sarah Rees (Time of Iron, 2024)
This adult epic fantasy debut from Sarah Rees Brennan puts the reader in the villain's shoes, for an adventure that is both "brilliant" (Holly Black) and "supremely satisfying" (Leigh Bardugo). Expect a rogue's gallery of villains including an axe wielding maid, a shining knight with dark moods, a homicidal bodyguard, and a playboy spymaster with a golden heart and a filthy reputation. When her whole life collapsed, Rae still had books. Dying, she seizes a second chance at living: a magical bargain that lets her enter the world of her favorite fantasy series. She wakes in a castle on the edge of a hellish chasm, in a kingdom on the brink of war. Home to dangerous monsters, scheming courtiers and her favourite fictional character: the Once and Forever Emperor. He's impossibly alluring, as only fiction can be. And in this fantasy world, she discovers she's not the heroine, but the villainess in the Emperor's tale. So be it. The wicked are better dressed, with better one-liners, even if they're doomed to bad ends. She assembles the wildly disparate villains of the story under her evil leadership, plotting to change their fate. But as the body count rises and the Emperor's fury increases, it seems Rae and her allies may not survive to see the final page. THIS IS A TALE FOR EVERYONE WHO'S EVER FALLEN FOR THE VILLAIN...